ADSORBEN MAGNETIK Fe3O4/SiO2 NPCS TERMODIFIKASI GUGUS TIOL DAN KAJIAN ADSORPSINYA TERHADAP ION [AuCl4]- - , YUSRAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Magnetic adsorbent of Fe3O4/SiO 2 NPCS modified with thiol (-SH) group for [AuCl 4 ] - ion adsorption was synthesized. Fe3O4 particles were prepared by co precipitation method under mechanical stirring, then further coated with SiO 2 by acid hydrolyzing of Na 2SiO3 under N 2 bubbling. SiO 2 coating functions to avoid the agglomeration of Fe3O4 particles by forming Fe3O4/SiO 2 in nanoscale and to protect the Fe 3O4 core for being dissolved in acid solution. The coated particle then was modified with thiol group (-SH) using 3-MPTMS through silanization reaction. FT-IR, XRD, TEM and EDS instruments were employed to characterize the resulted adsorbent. The results showed that SiO2 coated the Fe 3O4 core yielding magnetic core shell in 10-20 nm scale. Thiol group signed on the surface of core shell based on Infrared and EDX analysis. The maximum uptake towards [AuCl 4 ] - ion was reached at pH 3 which followed Langmuir isotherm model with maximum adsorption capacity ( ) of 114.81 mg/g and adsorption free energy (âGâ°) of 24.78 kJ/mol. Desorption agent of 8 mg of thiourea in 100 ml HCl 1M enabled to desorbs 43 mg/g of adsorbed [AuCl 4 ] - ion when the adsorbed concentration was 68.35 mg/g. Both adsorption and desorption were assumed as chemical bonding through complex coordination bonding formation based on Pearsonâs hard-soft acid-base principles.